METACESTODES OF PARVITAENIA MACROPEOS (CYCLOPHYLLIDEA, GRYPORHYNCHIDAE) IN AUSTRALOHEROS FACETUS (PISCES, CICHLIDAE) IN BRAZIL - Alves Pinto, Hudson (2011)
During studies of helminth parasites of Australoheros facetus (Jenyns, 1842) collected in the Pampulha dam, Belo Horizonte, Minas Gerais, Brazil, in June and July 2011, it was verified the natural infection of these fishes by larval cestodes. From 20 specimens of A. facetus analyzed, 13 (65%) presented metacestodes in the intestine, with the mean intensity 2.69 (1-7) and mean abundance 1.8 (0-7). After morphological characterization, the parasites were identified as Parvitaenia macropeos (Wedl, 1855). This is the first report of metacestodes of Parvitaenia in Brazil and P. macropeos in South America. Australoheros facetus is a new host known for P. macropeos.